Far-lateral Vascularized Rib Graft for Cervical and Lumbar Spinal Arthrodesis: Cadaveric Technique Description. Issue 4 (April 2019) - Bohl, Michael A.; Hlubek, Randall J.; Turner, Jay D.; Kakarla, U. Kumar; Preul, Mark C.; Reece, Edward M.
Abstract : Background: Rotational vascularized autografts are ideal for achieving spinal arthrodesis because they maintain bony vascularization while avoiding the morbidity and challenges of free-tissue transfer. Although proximal ribs are ideal candidates for vascularized bone grafts, their use is restricted to the thoracic spine. This study describes a novel technique for harvesting lateral rib grafts on an intercostal pedicle for use in cervical and lumbar posterolateral arthrodesis. Methods: Six cadaveric dissections were performed (2 included upper and all 6 included lower rib dissections). Measurements included graft width and thickness, distance reached from harvest level to the top of the graft, and ipsilateral and contralateral spine levels reached by the graft. Results: Overall, 60 lateral rib grafts were harvested. Intercostal vessel pedicles were torn during harvest in 4/48 (8.3%) of the lower rib and 5/12 (41.7%) of the upper rib grafts. Mean measurements of successful upper rib grafts were 1.4 ± 0.12 cm × 0.5 ± 0.15 cm (width × thickness), 14.1 ± 2.79 cm (distance) reached, and C2 (occiput–C4) reached ipsilaterally and C3 (occiput–C5) reached contralaterally. Mean lower rib graft measurements were 1.4 ± 0.26 cm × 0.4 ± 0.15 cm (width × thickness), 18.0 ± 6.19 cm (distance), S1 (L1–S2) reached ipsilaterally, and L4 (L1–S1) reached contralaterally. Conclusions: It is technically feasible to rotate a far-lateral rib graft on an intercostal pedicle into the posterolateral cervical or lumbar spine for the augmentation of arthrodesis. Upper ribs seem to be more difficult to harvest and rotate while keeping the intercostal pedicle intact than lower ribs.